2021
DOI: 10.3389/fmars.2021.615929
|View full text |Cite
|
Sign up to set email alerts
|

Advances on Coastal and Estuarine Circulations Around the Changjiang Estuary in the Recent Decades (2000–2020)

Abstract: Advances on the circulation in the Changjiang Estuary and adjacent East China Sea (ECS) and Yellow Sea (YS) coastal waters in the recent decades (2000–2020) are synthesized in this review. The circulation over the complicated bathymetry in the region is locally driven by winds, tides, as well as riverine discharge, and is remotely influenced by shelf currents between the 50 and 100-m isobaths through the cross-shelf exchanges. The interchange of the momentum and the freshwater pathway inside the Changjiang Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 181 publications
(267 reference statements)
2
18
0
Order By: Relevance
“…The resulting P limitation in offshore waters expanded to Jeju Island in the northeast at the seasonal peak of the plume expansion (Figure 5). This large-scale distribution of surface nutrients and their limitation effect on primary production are consistent with the main seasonal circulation (Bai et al, 2014;Liu et al, 2021), with observations off the CE (Li et al, 2009;Wang et al, 2015), as well as with observations of Changjiang-related excess NO3 in the northeastern ECS (Wong et al, 1998) and near Jeju Island (Kodama et al, 2017;Moon et al, 2021). Despite its large-scale distribution, P limitation was most prominent over the southwestern part of the Yangtze Bank (Figure 4) from mid-July to early August (Figure 6), i.e., around the peak of the discharge.…”
Section: Distribution Of P Limitation On the Shelfsupporting
confidence: 82%
See 1 more Smart Citation
“…The resulting P limitation in offshore waters expanded to Jeju Island in the northeast at the seasonal peak of the plume expansion (Figure 5). This large-scale distribution of surface nutrients and their limitation effect on primary production are consistent with the main seasonal circulation (Bai et al, 2014;Liu et al, 2021), with observations off the CE (Li et al, 2009;Wang et al, 2015), as well as with observations of Changjiang-related excess NO3 in the northeastern ECS (Wong et al, 1998) and near Jeju Island (Kodama et al, 2017;Moon et al, 2021). Despite its large-scale distribution, P limitation was most prominent over the southwestern part of the Yangtze Bank (Figure 4) from mid-July to early August (Figure 6), i.e., around the peak of the discharge.…”
Section: Distribution Of P Limitation On the Shelfsupporting
confidence: 82%
“…For instance, in the somewhat similar Mississippi River plume in the northern Gulf of Mexico, seasonal P limitation is observed around mid-shelf at the peak of annual production, between a light limited area in the vicinity of the river and the N-limited downstream/offshore waters (Laurent et al, 2012;Sylvan et al, 2006). Phytoplankton growth limitation in the ECS followed these general patterns along the CE-JI transect, but over a larger spatial scale given the dispersive nature of the Changjiang plume (Liu et al, 2021).…”
Section: Distribution Of P Limitation On the Shelfmentioning
confidence: 77%
“…The shelf currents play a role in modulating the river plume and seaward sediment dispersion (Liu et al, 2021). To the north of the CD, the Subei Currents are perennially southward, which can drive sediment transport from the abandoned Yellow River delta towards the CD, supplying sediment in building up the northern delta plains (Wang et al, 2020;Shang et al, 2021), even to the depocenter zone (Liu et al, 2010b).…”
Section: Coastal Ocean Dynamicsmentioning
confidence: 99%
“…The Changjiang runoff is the largest discharge into the ECS shelf ocean and cannot be neglected in the role of the formation of low‐salinity shelf water. Observations frequently showed a patchlike structure of the low‐salinity water detached from the Changjiang Diluted Water (CDW) plume (Gao et al., 1992; Liu et al., 2021b; Moon et al., 2010; Zhu et al., 1998). Isobe et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Changjiang runoff is the largest discharge into the ECS shelf ocean and cannot be neglected in the role of the formation of low-salinity shelf water. Observations frequently showed a patchlike structure of the low-salinity water detached from the Changjiang Diluted Water (CDW) plume (Gao et al, 1992;Liu et al, 2021b;Moon et al, 2010;Zhu et al, 1998). Isobe et al (2004) suggested that the isopycnal surface of 24.5 𝐴𝐴 𝐴𝐴𝜃𝜃 may be the deepest layer of the Kuroshio isopycnals outcropping to the sea surface onto the ECS shelf in spring.…”
mentioning
confidence: 99%